The influence of ethical leadership on project success in educational entrepreneurial ventures at a South African University of Technology - Nkomzwayo, Samkeziwe Esther (Cape Peninsula University of Technology, 2022)
The desire for educational entrepreneurship in Africa has increased over the past decade. Leaders in education must also uphold ethical principles and have a genuine desire to help students complete their education. Educational entrepreneurship in universities and colleges only succeeds when it is applied ethically; otherwise, it harms the students who receive the educational programmes. In educational institutions, ethical leadership is the practice of having a favourable impact on educational leaders' decisions that are right and appropriate for the greater societal and economic benefit. Therefore, ethical educational leaders are more likely to respect and treat their students fairly by considering their needs and rights. Unethical leadership practices have had the greatest impact on educational entrepreneurship projects, particularly those at state universities. Higher education institutions suffer reputational harm when unethical educational leaders engage in the creation, selection and launch of academic programmes. The impact of ethical leadership on project success in entrepreneurial educational programmes at South African universities is, therefore, intriguing to comprehend. The main objective of this study is to investigate how ethical leadership affects project success in educational entrepreneurship initiatives at a South African University of Technology. The study's conclusions are presented, along with ideas for additional research directions and advice on how to improve project success rates through ethical leadership. One of the study's main findings is that the management of the faculty was pleased with the success of the projects and programmes it had started in the field of education. Thus, it is likely that the students will complete their degrees on time. It is recommended that university administrators implement effective employee feedback systems to improve working conditions. Furthermore, all faculty members should receive formal training and induction on how to "do the right thing the first time" to prevent underperformance.
Thesis (MTech (Business Administration in Project Management))--Cape Peninsula University of Technology, 2022
Keywords: Ethical leadership; Entrepreneurship -- Study and teaching (Higher); Educational leadership -- Moral and ethical aspects; Success in business